The hitch : a novel - Levine, Sara (Roxane Gay Books, 2026)
"From the author of the cult classic Treasure Island!!!, a seductively outlandish novel following a woman as she attempts to exorcise the spirit of a dead corgi from her nephew and renegotiate the borders of her previously rational world. As an antiracist, Jewish secular feminist eco-warrior, Rose Cutler knows the right way to do everything, including parent her six-year-old nephew Nathan. But while she's looking after him in his parents' absence, things veer disastrously off course-Rose's Newfoundland attacks and kills a corgi at the park, and Nathan starts acting strangely: barking, overeating, talking to himself. Rose mistakes this for repressed grief over the corgi's death, but Nathan insists he isn't grieving, and the corgi isn't dead. Her soul leaped into his body, and she's living inside him. Now, Rose must banish the corgi from her nephew before his parents return. From the outrageously original mind of Sara Levine, The Hitch is a delightfully raucous comedy about loneliness, bad boundaries, and the ill-fated ambition of micromanaging everything and everyone around you"-- Provided by publisher.